Interleukin 8 Association with respiratory syncytial virus bronchiolitis: a systematic review and meta-analysis - Peng, Li; Meng, Fanzheng; Liu, Yuhuan; Zhang, Li (Cellular and Molecular Biology, 2020)
Infants with the respiratory syncytial virus (RSV) and human rhinovirus respiratory infection (HRV) produce inflammatory interleukins (ILs) in the respiratory epithelium. The aim of this study was to evaluate the levels of interleukin-8 in RSV negative and RSV positive patients. This study search was conducted without a time limit until 2020 through the databases of PubMed, Wiley, Springer, ScienceDirect and Google Scholar search engines, by two researchers independently. The random-effects model was used to compare of interleukin-8 in RSV negative vs. RSV positive patients, using Revman software version 5 meta-analysis software. Totally, 921 patients were evaluated (207 RSV-negative and 714 RSV-positive). The mean concentration of IL8 in RSV positive patients was 15.02 pg/ml (95% CI: 13.68- 16.35%). According to the meta-analysis results, the standardized mean difference (SMD) of IL8 concentration between RSV-positive and negative patients was 6.31 pg/ml) (95% confidence interval: 2.50- 10.13%). subtotal analysis of the IL8 laboratory assessment method revealed that there was no significant SMD deference in the studies that have used chemiluminescence (P=0.21). while IL8 concentrations were significantly higher in RSV positives in ELISA and Magnetic bead-based assays (P<0.05). It appears that RSV positive patients may have greater levels of IL8 than RSV negative ones; whereas the synthesis of IL8 tends to be more secreted into the nasopharyngeal space; whereas the evaluation approach can also affect the results.